If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6g+7=2(-2g+1)-2g-9
We move all terms to the left:
-6g+7-(2(-2g+1)-2g-9)=0
We calculate terms in parentheses: -(2(-2g+1)-2g-9), so:We get rid of parentheses
2(-2g+1)-2g-9
We add all the numbers together, and all the variables
-2g+2(-2g+1)-9
We multiply parentheses
-2g-4g+2-9
We add all the numbers together, and all the variables
-6g-7
Back to the equation:
-(-6g-7)
-6g+6g+7+7=0
We add all the numbers together, and all the variables
14!=0
There is no solution for this equation
| 2-(-2s)=0 | | 2r-6+5r=3+7r+7 | | 0.1x+0.3+2/0.5=0.5 | | 1×1.01^x=2 | | 0=2y+30 | | v-2=v-11 | | 50x=x^2+500 | | -9+45=6(x-5) | | 2(3x-7)=6x+14 | | 3y(3y-5)(2y-7)=0 | | 13g-5g+-11g-7=5 | | 2x+4x+6x=72 | | 8b+12.3-b=8.1+7b+4.2 | | 11=2(c+2)+3 | | 36+4x=2x-7(1-7) | | a-19=4 | | 2x+4x6x=72 | | -3s+25=25 | | 5n^2+10n-113=7 | | M1=(95+7x) | | 4(2-d)=3(2+d) | | X^2-120x-625=0 | | M2=(55-x) | | -59=-6x-5x-4 | | 5m-1-3m=2m+5 | | M2=(55-x)• | | -6(-4x-2)=60 | | 2w+7-w=3+w+4 | | 12x-2=15x-17 | | (7x-4)=(5x+19) | | 27x=26x+4 | | -7(-3b-4)=-119 |